The bacterial and archaeal communities of flies, manure, lagoons, and troughs at a working dairy - Crippen, Tawni L.; Kim, Dongmin; Poole, Toni L.; Swiger, Sonja L.; Anderson, Robin C. (Frontiers in Microbiology, 2024)
BACKGROUND: Fundamental investigations into the location, load, and persistence of microbes, whether beneficial or detrimental, are scarce. Many questions about the retention and survival of microbes on various surfaces, as well as the load necessary for spread, exist. To answer these questions, we must know more about where we to find various microbes and in what concentrations, the composition of the microbial communities, and the extent of dissemination interactions between the various elements. This study investigates theinvestigated the diversity, composition, and relative abundance bacterial and archaeal speciesof the communities associated with manure, lagoons, troughs, house flies, and stable flies present at a dairy implementing two different free stall management systems, flow-through and cross-vent. Whole Shotgun metagenomicsgenome sequencing at the community level was used to compare the microbiomes within the dairy, allowing confident interpretation at the species level. RESULTS: The results tell us that there was a significant difference in microbial composition between not only each of the dairy elements, but also management styles. The primary exception was the microbiomes of the house and stable fly. Their compositions heavily overlapped with one another, but interestingly, not with the other components sampled. Additionally, both species of flies carried more pathogens than the other elements of the dairy, indicating that they may not be sharing these organisms amongst the other components, or that the environments offered by the other components are unsatisfactory for survival of some pathogens. CONCLUSIONS: The lack of overlapping pathogen profiles suggests a lack of transfer from flies to other dairy elements. Together with dairy health data showing low incidence of disease suggests minimal sharing of the bacteria by the flies at a level required for infection given this dairy’s health program. While flies did carry a multitude of pathogenic bacteria, the mere presence of that bacteria associated with the flies did not necessarily translate into high risk leading to morbidity and mortality at this dairy. Thus, using flies as a sole sentinel of dairy health may not be appropriate for all bacterial pathogens or dairies.